Juvenile dermatomyositis and celiac disease. A rare association. - Molnár, K.; Torma, K.; Siklós, K.; Csanády, K.; Korponay-Szabó, I.; Szalai, Z. (European Journal of Pediatric Dermatology, 2006)
Recently a few cases of patients with dermatomyositis (DM), juvenile DM (JDM) and celiac disease (CD) have been reported. We describe a new case, a child with a seven-year history of JDM who developed CD. The child showed typical signs of JDM at the age of 4. She underwent relapses of JDM with muscle weakness, skin symptoms and laboratory findings every 1-2 years. Different immunosuppressive and cytostatic agents were used. Because of epigastric pain she underwent examinations. The latter showed lactose intolerance, as well as IgA class anti-endomysium antibodies, anti-reticulin antibodies, celiac specific jejunal autoantibodies and transglutaminase autoantibodies. The duodenum biopsy showed mucosal atrophy and hypertrophy of the crypts. CD was diagnosed and a gluten-free diet was started. Patients with DM/JDM should be screened for CD by antibody testing to determine the frequency of silent CD in patients with DM/JDM.